S108 Expert consensus on diagnostic criteria and tertiary service requirements for bronchiectasis. (2nd December 2011) - Holme, J; Bianchi, S; Clifton, I; De-Soyza, A; Edenborough, F; Peckham, D; Pirzada, O; Walker, P; Walshaw, M; Niven, R
Abstract : Introduction: There are no agreed diagnostic criteria for bronchiectasis and no stated minimum requirements for a tertiary service. The Northern Bronchiectasis Group aimed to use the validated RAND technique to form consensus opinions on these issues. Method: Following literature review, a questionnaire was devised containing 89 statements relevant to the topics above. Eight expert members rated their level of agreement with the statements from 1 (not relevant) to 9 (mandatory). Following a group debate about these statements, the experts re-structured some statements then re-rated the questionnaire. Consensus agreement, indifference or disagreement was reached if 7/8 members' scores were in the 7–9, 4–6 or 1–3 ranges respectively. Results: There was consensus agreement for 31/89, consensus indifference for 5/89 and consensus disagreement for 12/89 statements. Consensus was not reached for 41/89 statements. It was agreed daily sputum production would prompt investigation for bronchiectasis, CT was always necessary, and the following factors, support the diagnosis: bronchoarterial ratio >1.0, non-tapering bronchi, thickened airway walls, irreversible changes. It was agreed that a tertiary service should provide: access to HRCT, spirometry, routine and fungal sputum cultures, ciliary function testing; functional antibodies and immunoglobulins for all, antibiotic & hypertonic saline nebuliser challenges, nebuliser loan and maintenance, home iv antibiotic service (preferably by patients in their own homes), portacath insertion, physiotherapy at least annually, access to a dietician, immunologist, microbiologist with an interest in bronchiectasis and pulmonary rehabilitation. Specialist nurses could see selected patients and separate clinics are desirable for patients colonised with pseudomonas. There was indifference to the availability of telephone consultations, posted sputum analysis, iv antibiotic service based in the community (not in patients' home), a patient support group and patient educational sessions. Consensus was not reached regarding if respiratory infection, bronchoarterial ratios of >1.5 or >2.0 or abnormal spirometry are necessary to diagnose bronchiectasis; or if a consultant should see patients at most visits, iv antibiotics could be given by a nurse in the patients home and if access to palliative care was necessary in a tertiary service. Conclusion: Comprehensive consensus statements regarding the diagnostic criteria for bronchiectasis and tertiary service requirements have been formed.